2017
DOI: 10.1111/jsbm.12316
|View full text |Cite
|
Sign up to set email alerts
|

Commitment Escalation to a Failing Family Business

Abstract: The overarching intent of this manuscript is to heighten awareness to the concept of commitment escalation as it bears on a failing family business. Specifically, drawing on the concept of emotional ownership, together with self‐justification arguments, we (1) identify factors considered to be most forceful in contributing to the presence of commitment escalation and thus, resistance to change in a failing family business, and (2) model these related factors in a form that can serve heuristically to stimulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 98 publications
(269 reference statements)
4
48
1
1
Order By: Relevance
“…Performance threats should intensify the difference between family and nonfamily owners in relation to the option of business exit versus continuation. SEW presents a psychological barrier to the firm’s extinction and causes family owners to tolerate and even justify increasingly negative performance cues while escalating their commitment to the business without resorting to exit (see Chirico, Salvato, Byrne, Akhter, & Arriaga Múzquiz, 2018). In this regard, Lansberg (1988), DeTienne and Chirico (2013), and Sharma and Manikutty (2005) argue that family owners often avoid or deny such a reality, preferring instead to continue the operations of a failing business for affective rather than financial reasons.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Performance threats should intensify the difference between family and nonfamily owners in relation to the option of business exit versus continuation. SEW presents a psychological barrier to the firm’s extinction and causes family owners to tolerate and even justify increasingly negative performance cues while escalating their commitment to the business without resorting to exit (see Chirico, Salvato, Byrne, Akhter, & Arriaga Múzquiz, 2018). In this regard, Lansberg (1988), DeTienne and Chirico (2013), and Sharma and Manikutty (2005) argue that family owners often avoid or deny such a reality, preferring instead to continue the operations of a failing business for affective rather than financial reasons.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The basic claim of social identity theory is that individuals who identify themselves with particular social groups, such as a family business, favor those groups (Ashforth and Mael, ; Tajfel et al , ; Turner, ). Social identity refers to the groups to which one belongs (Chirico et al , forthcoming) and arises because individuals classify themselves and others into social categories (Turner et al , ). These classifications enable individuals to make sense of their social environment and to define themselves in relation to others (Ashforth and Mael, ; Deephouse and Jaskiewicz, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…First, the family's long‐term involvement and the common practice of including the family's name in the business' name enhance its members' identification with the family firm as their social group; indeed, evidence shows that business families strongly identify with their firms (Deephouse and Jaskiewicz, ). Such identification is often a function of the family's needs and demands (Miller, Breton‐Miller, and Lester, ) such that the business becomes an extension of the family and its members (Chirico et al , forthcoming). By identifying themselves with the business, the family comes to define itself in terms of a perceived social group or category (Mael and Ashforth, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Both internal factors and external contexts can serve to influence whether or not one persists in, or exits from, self‐employment (Gimeno et al ). Although evidence has indicated that individual factors, such as personal values (Holland and Shepherd ) and socioemotional wealth (Chirico et al ; Parastuty et al ), as well as expected financial and emotional costs (Shepherd, Wiklund, and Haynie ) can all effect whether or not individuals exit self‐employment, it is also important to consider the impact that external contexts and the life‐cycle stage of an individual can have on the decision to persist in self‐employment (Gimeno et al ).…”
Section: Introductionmentioning
confidence: 99%